Retracted: Prevalence of sexually transmitted infections and associated risk behaviors in prisoners: A systematic review - SeyedAhmad SeyedAlinaghi; Zahra Pashaei; Ensiyeh Rahimi; Solmaz Saeidi; Pegah Mirzapour; Tayebeh Noori; Afsaneh Ghasemzadeh; Arian Afzalian; Mohsen Dashti; Pedram Habibi; Behnam Farhoudi; Narjes Aghaie; et al. (Health Science Reports, 2022)
Abstract Background and Aims Sexually transmitted infections (STIs) are one of the major health concerns globally. Generally, prisoners are at higher risks for STIs due to risk factors including; drug‐use, high‐risk sexual behaviors, densely populated prisons, and poor living conditions. Therefore, we aimed to conduct a systematic review to evaluate the existing data on STI prevalence, and its associated risk factors among prisoners. Methods We conducted a systematic search of the literature using the keywords in Scopus, PubMed, Web of Science, and Google Scholar online databases. We selected all the relevant original studies in English through title/abstract and full‐text screening process.‎ Results Based on the inclusion and exclusion criteria, we selected and reviewed 32 studies out of 96 identified papers. The most important STI‐associated risk factors among prisoners were drug use, low educational levels, and unsafe sex. The prevalence of STIs was heterogenous in selected studies and was reported as follows; Human Immunodeficiency Virus (HIV) (0%−14.5%), hepatitis B viruses (HBV) (0.04%−27.23%), hepatitis C viruses (HCV) (0.17%−49.7%), Syphilis (0.2%−22.1%), Chlamydia Trachomatis (CT) (1.02%−6.7%), Gonorrhea (0.6%−7.8%), and herpes simplex virus‐2 (HSV‐2) 22.4%. Conclusion This systematic review indicates that the prevalence of STIs (HIV, HBV, HCV, Syphilis, Chlamydia Trachomatis, Gonorrhea, and HSV‐2) among prisoners appears to be higher than the general population, with drug abuse, low educational levels, and unsafe sex as major risk factors.